(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this study was to explore the participation of teachers in CPD and its impact on teaching and learning. Using mixed method approach both quantitative and qualitative data were gathered. Quantitative data were collected from 624 primary schools teachers who were selected randomly. Qualitative data were collected from teachers, school principals, supervisors and education officers. Questionnaire, interview and FGD were used to collect data. To analyse the quantitative data, mean, independent sample t test and one way ANOVA were used. The qualitative data were used were analysed and triangulated with quantitative data. The findings of the study showed that teachers participated in collaborative and school based CPD activities, especially in study group and informal dialogue, to a moderate level. Their participation in action research and off school workshops were found rare. The result also revealed that active learning and continuous assessment method were more emphasised contents in their CPD opportunities. Content knowledge was not given equal emphasis to active learning and continuous assessment methods. Critical to this study is that the impact of CPD was found to be low. Even though, emphasis has been given to school based CPD and teachers could participate in collaborative work or group activity and informal dialogue, significant change was not observed on teachers change and students learning outcomes. The findings of this study imply that well established professional and material support should be established at school as well as at respective education hierarchy so that the focus and the support for CPD will be effective and sustainable.